Improving chronic illness self-management with the Apsáalooke Nation: Development of the Báa nnilah program. (December 2019) - Held, Suzanne; Hallett, John; Schure, Mark; Knows His Gun McCormick, Alma; Allen, Sarah; Milne-Price, Shauna; Trottier, Coleen; Bull Shows, Brianna; Other Medicine, Lucille; Inouye, Jillian
Abstract: Rationale: Since 1996, members of the Apsáalooke (Crow) Nation and faculty and students at Montana State University have worked in a successful community-based participatory research (CBPR) partnership, leading to increased trust and improvements in health awareness, knowledge, and behaviors. As major barriers to health and healthy behaviors have caused inequities in morbidity and mortality rates for multiple chronic diseases among the Apsáalooke people, community members chose to focus the next phase of research on improving chronic illness management. Objective: Existing chronic illness self-management programs include aspects inconsonant with Apsáalooke culture and neglect local factors seen as vital to community members managing their health conditions. The aim of this study was to use CBPR methods grounded in Apsáalooke cultural values to develop an intervention for improving chronic illness self-management. Method: Community members shared stories about what it is like to manage their chronic illness, including facilitators and barriers to chronic illness management. A culturally consonant data analysis method was used to develop a locally-based conceptual framework for understanding chronic illness management and an intervention grounded in the local culture. Results: Components of the intervention approach and intervention content are detailed and similarities and differences from other chronic illness management programs are described. Conclusions: Our collaborative process and product may be helpful for other communities interested in using story data to develop research projects, deepen their understanding of health, and increase health equity. Highlights: Use of story data to develop a chronic illness self-management program. Intervention based on Apsáalooke cultural strengths and values. Uses a trauma-informed approach for both historical and current trauma and loss. Uses a community-based participatory research approach.